Physiological responses of sugar-apple seedlings under saline wastewater irrigation and NPK doses - Adailha Torres Souza, Antônia; Mendonça, Vander; Pereira de Paiva, Emanoela; Targino Oliveira Pereira, Kleane; da Silva Lima Reges, Keivianne; Carantino Lucena Moreira, Romulo; Dantas Fernandes, Pedro; Vanies da Silva Sá, Francisco (Revista Ciência Agronômica, 2023)
Salt stress stands out as one of the main limiting factors in agricultural production in arid and semi-arid regions, due to its osmotic and ionic effects on plants. In this context, the objective was to evaluate the physiological responses of sugar-apple seedlings irrigated with saline wastewater under different doses of NPK. The experiment was carried out in a greenhouse, in a randomized block design, in a 3 x 5 factorial scheme, with four replicates. Three irrigation waters were tested: local-supply water (control), reject brine and fish farming effluent, and five doses of NPK, referring to the proportions of 25, 50, 75, 100, and 125% of the N:P:K fertilizer recommendation of 100:300:150 mg dm-3. Seedlings were cultivated in 2-dm3 containers filled with sandy soil for 90 days after sowing. At the end of this period, gas exchange, chlorophyll fluorescence, and biomass accumulation were evaluated. The use of reject brine and fish farming effluent to irrigate sugar-apple seedlings reduced photosynthetic activity and biomass accumulation. The best physiological responses and biomass accumulation occur at NPK doses of 75% (75:225:112.5 mg dm-3 of N:P:K) for seedlings irrigated with local-supply water, 60% (60:180: 90 mg dm-3 of N:P:K) for seedlings irrigated with reject brine, and 40% (40:120:60 mg dm-3 of N:P:K) for seedlings irrigated with fish farming effluent.